Pengaruh Strategi Pembelajaran Aktif Teknik Team Quiz dan Snowball Throwing terhadap Hasil Belajar Matematika - Desy Bangkit Arihati (LPPM STKIP Kusuma Negara, 2018)
The aim of this research is to know the result of learning mathematics by using Team Quiz and Snowball Throwing techniques of active learning strategies and using conventional learning and the influence of Team Quiz and Snowball Throwing technique of active learning strategies toward the result of study in mathematics. The method is quasi experiment with the subject of this research is students class VIII of 203 State Junior High School Kalisari, East Jakarta. The technique of sample taking used in this study is cluster random sampling technique. Technique of data analysis which used in this research is t-test, and based on t-test calculation, it shows thitung = 5,32 and ttabel = 1,99 with significant level 5% or (a = 0,05) and degree of freedom (db = 70) it means thitung > ttabel (2,37 > 1,66). So, it can be concluded that average of achievement of students whom given Team Quiz and Snowball Throwing techniques is higher than the achievement of students whom given conventional learning